1995
DOI: 10.1126/science.269.5225.822
|View full text |Cite
|
Sign up to set email alerts
|

High- 3 He Plume Origin and Temporal-Spatial Evolution of the Siberian Flood Basalts

Abstract: An olivine nephelinite from the lower part of a thick alkalic ultrabasic and mafic sequence of volcanic rocks of the northeastern part of the Siberian flood basalt province (SFBP) yielded a (40)Ar/(39)Ar plateau age of 253.3 +/- 2.6 million years, distinctly older than the main tholeiitic pulse of the SFBP at 250.0 million years. Olivine phenocrysts of this rock showed (3)He/(4)He ratios up to 12.7 times the atmospheric ratio; these values suggest a lower mantle plume origin. The neodymium and strontium isotop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
81
1

Year Published

2003
2003
2021
2021

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 146 publications
(84 citation statements)
references
References 30 publications
2
81
1
Order By: Relevance
“…There was no documented subsequent successful rifting (apart from possible continental rifting in the Kazakhstan basin [37]) which may in part be responsible for the absence of an 'age tail', as found for instance in the Paraná. Basu et al [12] determined an 40 Ar/ 39 Ar age of 253.0 ± 2.6 Ma in alkalic-ultramafic lavas infilling a pre-existing Late Permian graben in the Northeast; this might be an indication of a slightly older onset of volcanism, though we find little convincing evidence, for this (Wignall's figure 5 [190], comparing the timing of the various events, is misleading, because it ignores these uncertainties). The basal parts of the Siberian traps contain a high proportion of fragmental basaltic lavas.…”
Section: The Siberian Trapscontrasting
confidence: 63%
“…There was no documented subsequent successful rifting (apart from possible continental rifting in the Kazakhstan basin [37]) which may in part be responsible for the absence of an 'age tail', as found for instance in the Paraná. Basu et al [12] determined an 40 Ar/ 39 Ar age of 253.0 ± 2.6 Ma in alkalic-ultramafic lavas infilling a pre-existing Late Permian graben in the Northeast; this might be an indication of a slightly older onset of volcanism, though we find little convincing evidence, for this (Wignall's figure 5 [190], comparing the timing of the various events, is misleading, because it ignores these uncertainties). The basal parts of the Siberian traps contain a high proportion of fragmental basaltic lavas.…”
Section: The Siberian Trapscontrasting
confidence: 63%
“…3). Basu et al (1995) (Renne and Basu, 1991). However, Kamo et al (2003) reported the UPb perovskite age of 251.7 ± 0.4 Ma for the Arydjansky suite, which is indistinguishable from the Permo-Triassic U-Pb zircon and baddeleyite age 251.2 ± 0.3 Ma for the Noril'sk-I orebearing intrusion at Noril'sk-Kharaelakh subprovince (Kamo et al, 1996).…”
Section: Duration Of Siberian Traps Fbp Magmatismmentioning
confidence: 99%
“…3. Relative probability distribution of 40 Ar/ 39 Ar ages (after Ivanov et al, 2006) and original ages (from Baksi and Farrar, 1991;Basu et al, 1995;Dalrymple et al, 1995;Reichow et al, 2002;Renne and Basu, 1991;Venkatesan et al, 1997;Walderhaug et al, 2005). The Permo-Triassic boundary is from Renne et al (1995).…”
Section: Timing Of Initial Eruptions Within the Siberian Traps Fbpmentioning
confidence: 99%
“…Published 40 Ar/ 39 Ar determinations (whole-rock and plagioclase separates) exist for basalts from Noril'sk [14,22,23] , Putorana [14] , Maymecha-Kotuy [24] and the West Siberian Basin [25] (Figure 3 [16] at Meishan, China (see below). Zircons and baddeleyites from intrusions at Noril'sk, together with perovskite, zircon and baddeleyite from Maymecha-Kotuy, give U/Pb concordia ages that are slightly but significantly older than the 40 Ar/ 39 Ar ages.…”
Section: The Age Of the Siberian Trapsmentioning
confidence: 99%
“…Error propagation was established by including the uncertainty of each age as the square root of the sum of the squares of the errors. Sources of data: green symbols: Reichow et al [1] ; red symbols: Noril'sk [14,22,23] , Putorana [14] , Maymecha-Kotuy [24] , and West Siberian Basin [25] . Data for Meishan Bed 28 are from Reichow et al [1] .…”
Section: The Age Of the Siberian Trapsmentioning
confidence: 99%